Exploratory GABAa-informed control network modulates hyperarousal brain dynamics in chronic insomnia - Liyong Yu; Liang Gong; Xiaoqin Chen; Yuqi He; Rong Li; Xiaojuan Hong; Qi Zhang; Siyi Yu (Communications Biology)
Abstract Chronic insomnia disorder is characterized by hyperarousal, a heightened cortical activation pattern that disrupts normal sleep. While hyperarousal has been linked to altered brain state dynamics, the underlying neurobiological mechanisms remain poorly understood, particularly regarding the influence of inhibitory neurotransmitter signaling through GABAa receptors. This study demonstrates that hyperarousal in chronic insomnia is characterized by more frequent and unpredictable transitions between brain states compared to healthy controls, as revealed by hidden Markov modeling of resting-state functional MRI data. By conducting an exploratory integration of DTI-based structural connectivity and regional GABAa receptor distribution within a network control theory framework, we find that chronic insomnia is associated with a flattened energy landscape reflecting hyperarousal, indicating that less energy is required for the brain to transition between states. Notably, accounting for GABAa receptor distribution increases the control energy required for state transitions and is associated with greater stability in brain state dynamics. These findings provide neurobiological insights into hyperarousal in chronic insomnia, with an exploratory analysis suggesting a modulatory role of GABAergic signaling in shaping the brain’s dynamic dysfunction.